Knowledge Management In Malaysia: Issues And Challenges - Tehraninasr, Ali (2008)
This research mainly focuses on issues and challenges for successful knowledge management initiatives among Malaysian organizations. Being an exploratory study, this investigation tries to discover issues and challenges which are pertinent in the context of knowledge management initiatives amongs Malaysian organizations.